Advanced Flame Treatment: New opportunities for roll‐to‐roll functionalization of polymer films. (25th August 2022) - Holländer, Andreas; Mancinelli, Stefano
Summary: Flame treatments are applied on large industrial scale for the surface activation of polymers. The process of flame treatment of polymers can be improved by combining it with the treatment with an aerosol of a solution of a functional polymer. It was shown that it results in the covalent binding of the polymer molecules at the surface. This approach was demonstrated with PP and PET films as substrates and with poly(acrylic acid) (PAA) and poly(ethylene imine) (PEI) as a functionalizing polymers in continuous processes at up 50 m/min. PAA introduces carboxylic acid groups and PEI gives rise to amino groups at the surface. This approach opens up a completely new range of functionality, which is not accessible with a flame treatment only. The amino groups allow improved properties for the adhesive joining with epoxy or urethane resins, in lamination processes, or for metallization. The functionalization was found to be stable for at least one year of storage and it resists washing with water and isopropanol. Zusammenfassung: Moderne Flammbehandlung – Neue Möglichkeiten für die Rolle‐zu‐Rolle‐Funktionalisierung von Polymerfolien Flammenbehandlungen werden in großem industriellen Maßstab zur Oberflächenaktivierung von Polymeren eingesetzt. Der Prozess der Flammbehandlung von Polymeren kann verbessert werden, indem er mit der Einwirkung eines Aerosols einer Lösung eines funktionellen Polymers kombiniert wird. Es wurde gezeigt, dass dies zu einer kovalenten Bindung der Polymermoleküle an der Oberfläche führt. Dieser Ansatz wurde mit PP‐ und PET‐Folien als Substrate und mit Polyacrylsäure (PAA) und Polyethylenimin (PEI) als funktionalisierende Polymere in kontinuierlichen Prozessen mit Geschwindigkeiten von bis zu 50 m/min demonstriert. PAA führt Carbonsäuregruppen ein und PEI führt zu Aminogruppen auf der Oberfläche. Dieser Weg eröffnet einen völlig neuen Bereich der Funktionalität, der mit einer reinen Flammenbehandlung nicht zugänglich ist. Die Aminogruppen ermöglichen verbesserte Eigenschaften für die Verklebung mit Epoxid‐ oder Urethanharzen, in Laminierungsprozessen oder für die Metallisierung. Es wurde gezeigt, dass die Funktionalisierung mindestens ein Jahr lang stabil ist und dem Waschen mit Wasser und Isopropanol standhält.